Consumer Confusion. - Schwartz, Moisés J. (IMF Working Papers., 2008)
This paper was prepared for the World Bank 4th Annual Contractual Savings Conference (Washington DC, April 2008) co-organized by Gregorio Impavido (gimpavido@imf.org). The article shows that account transfers among pension administrators in Mexico barely respond to price or return considerations and in general has not improved the consumer's pension balance. Instead of strengthening competition through lower fees and higher returns for the consumer, AFORE switching has so far undermined the system and resulted in the destruction of value. Moreover, ""noisy"" evaluations of the product by the c.